Land Consolidation as an Instrument of Shaping the Agrarian Structure in Poland: A Case Study of the Wielkopolskie and Dolnośląskie Voivodeships - Markuszewska, Iwona (Quaestiones Geographicae, 2013)
Fragmentation of agricultural landscape is a specific feature of agrarian structure in Poland. Despite the fact that consolidation work has been carried out for years, the positive effects are still negligible. This is because land consolidation in Poland is encountering with a number of obstacles, which on the one hand, is cumbersome formal and legal policy, and on the other hand, disapproval of officials and farmers as well. These barriers unnecessarily prolong the proceeding, which is inherently long-term, sometimes takes years and not always is successfully completed. For this reason an effort was made to answer the question: how improving in land consolidation policy may look up the efficiency of land merging work in Poland? Two formal procedures were presented, on the basis of which land consolidation is carried out in two voivodeships: Wielkopolskie and Dolnośląskie. The study revealed the main obstacles and weaknesses in legal regulation. Additionally, open-interviews among farmers as well as local and regional land consolidation authorities, were undertaken. On the basis of the acquired data, a number of new suggestions to more successful land consolidation policy, were put forward. Finally, possible solutions to perk up the land unification work were established.